Assessing the equivalence between etomidate and seizure network dynamics in temporal lobe epilepsy. Issue 1 (January 2016) - Vega-Zelaya, Lorena; Pastor, Jesús; Tormo, Isabel; de Sola, Rafael G.; Ortega, Guillermo J.
Highlights: Etomidate mimics some network properties of temporal lobe epilepsy seizures. Network temporal imbalance is reproduced during both etomidate administration and seizures. Etomidate effects could be used as a proxy for ictal dynamics in fMRI studies. Abstract: Objective: Etomidate mimics some typical epileptic neurophysiological features, such as the appearance of spikes and high frequency oscillations, when it is administrated to epileptic patients. However, little is known about its influence on the underlying cortical network. An assessment of comparable cortical dynamics between seizures and etomidate would allow for a more detailed study of the network parameters underlying the ictal stage by using etomidate as a proxy. The objective of the present work is to show that temporal lobe seizures produce network changes comparable to the ones elicited by etomidate administration. Methods: Scalp and foramen ovale electrodes (FOE) recordings from nine temporal lobe epilepsy patients were analyzed under the complex network perspective. The clustering coefficients, average path lengths, density of links, modularity and spectral entropy were calculated during the pre-ictal and ictal stages and post-etomidate administration. Etomidate administration produced no seizure in any of the analyzed cases. Results: The density of lines (six of nine patients) and spectral entropy (eight of nine patients) displayed similar behavior to the preictal–ictal transition when etomidate effects altered the epileptic network (FOE + scalp). When considering only the mesial sub-network, changes induced by etomidate perfusion replicated the same type of imbalance observed during the ictal stage in the nine patient's sample and in eight out of nine regarding the preictal stage. Both statistical significance at a level of 1% and size effects, evaluated by using the standardized mean differences, show similar network changes during the preictal–ictal and preictal–etomidate transitions. Conclusions: Etomidate perfusion in patients with temporal lobe epilepsy induces network changes comparable to the changes resulting from seizures. Significance: The finding reported here could improve the study of network dynamics during the ictal phase, not only with electrophysiological methods, but also in other cases, such as functional magnetic resonance imaging.